Synthesis and characterization of new covalent chains of 2,5-bi-(4-alcoxyphenyl)-1,3,4-oxadiazole and its polymers and study of their liquid crystal properties (Journal of the College of Basic Education, 2022)
Research time Methods of preparation and chemical properties of cyclic derivatives 1,3,4- oxadiazole substituted at the site 2,5. What are the procedures for preparing liquid crystalline polymers from 1,3,4- oxadaya heterocyclic compounds and spectroscopic methods